2006
DOI: 10.1080/01904160600972605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seeding Rate and Nitrogen Fertilization on Proso Millet Under Dryland and Irrigated Conditions

Abstract: Proso millet (Panicum miliaceum L.) is a short-season grain crop in semi-arid regions of North and South America and Asia. The objective of this study was to evaluate seeding rates and nitrogen (N) fertilization on proso millet seed yield, crude protein levels, and biomass yield under irrigated and dryland conditions in a Mediterranean-type transition climate near Bursa, Turkey. Seeds per panicle, panicle length, seed weight per panicle, fertile tillers, protein yield, and plant height were also evaluated. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 2 publications
2
11
1
2
Order By: Relevance
“…The optimal root development in proso millet occurs in 80-120kg N ha -1 doses [19]. It has been determined in various researches that the nitrogen fertilizer application increased the dry matter yield [13], the crude protein content [20], [21], and the crude protein yield [8] in Panicum species. Baltensperger et al [22] suggested that, when proso millet follows wheat, it is generally recommended that 45kg ha-1 of nitrogen be applied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal root development in proso millet occurs in 80-120kg N ha -1 doses [19]. It has been determined in various researches that the nitrogen fertilizer application increased the dry matter yield [13], the crude protein content [20], [21], and the crude protein yield [8] in Panicum species. Baltensperger et al [22] suggested that, when proso millet follows wheat, it is generally recommended that 45kg ha-1 of nitrogen be applied.…”
Section: Resultsmentioning
confidence: 99%
“…Proso millet is well adapted to many soil and climatic conditions; it has a short growing season, and needs little water. It matures quickly, in 60-100 days [8], [9]. Baltensperger [5] was reported, it can be grown farther north than other millets and is adapted to high elevation plateaus and poor soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of millet proteins is higher than winter wheat proteins (Kalinová and Moudrý 2006). The millet is unpretentious crop, but its cultivation requires attention at stand foundation (Agdag et al 2006;Káš and Janovská 2011) as well as at its fertilization (Turgut et al 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Kanada'da kum darı, cin darı, yulaf ve arpa ile çalışan May et al (2007) Hassan et al (2000), değişik dozlarda azotlu gübre uygulanan cin darıda en yüksek bitki boyunu 4.5 kg N da -1 uygulamasında belirlemiş, yüksek azot dozunda bitki boyu artışı olmamıştır. Turgut et al (2006) da bu bitkide en yüksek bitki boyunu 6 kg N da -1 dozunda belirlenmişlerdir (66.6 cm). Kalaghatagi et al (2000), en yüksek kuru ot verimini 4.5 kg N da -1 gübre dozunda belirlemişlerdir.…”
Section: Materyal Ve Yöntemunclassified